Prohibition of Interfaith Marriage Registration: A Critique of Judicial Policy - Darryl Evan Brouwer; Muhammad Akrom Ramadhan; Ananda Lestari (Lex Journal: Kajian Hukum & Keadilan, 2026)
In 2023, the Supreme Court enacted the Supreme Court Circular Letter Number 2 of 2023 on Guidelines for Judges in Adjudicating Cases of Marriage Registration Requests between People of Different Religions and Beliefs (SEMA 2/2023). The SEMA 2/2023 prohibits judges from granting applications for the registration of interfaith marriages between individuals of different religions and beliefs. This judicial policy does not cohere with the reality that some religions in Indonesia do not strictly prohibit interfaith marriage. Thus, such judicial policy unjustifiably infringes on the human rights of the citizens. This research is conducted to analyze the inconsistency of the SEMA 2/2023 with the Marriage Law, the reality of religious diversity in Indonesia, and the human rights principle. This research is conducted as normative legal research using the statutory and conceptual approach. The finding of this research is that the SEMA 2/2023 is in line with the Marriage Law, the reality of religious diversity in Indonesia, and the human rights principle. Thus, the judge shall not enforce the SEMA 2/2023.